The adaptation towards climate change impacts among islanders in Malaysia - Ahmad, Nobaya; Mohamed Shaffril, Hayrol Azril; Abu Samah, Asnarulkhadi; Idris, Khairuddin; Abu Samah, Bahaman; Hamdan, Mas Ernawati (Elsevier, 2020)
The climate change phenomenon has been occurring in every part of the world, including Malaysia. In particular, changes such as rising temperature, sea level rise, and unstable rain pattern are proven to affect the socio-economic routine of the community. Hence, it is necessary to learn how to adapt to it, especially those who heavily rely on nature stability. The present study examined the adaptation towards climate change among islanders in Malaysia. In addition, the current research was performed quantitatively using a developed questionnaire as the main data collection tool. In this case, a total of 400 islanders were selected as the respondents through a multi-stage sampling technique. The results revealed that the respondents recorded a moderate to high mean score for adaptation aspects namely awareness, dependency and structure. Accordingly, a number of recommendations that were highlighted can be utilized as a basis to develop community adaptation policy that is in line with the islanders' need, ability, and interests.